2016
DOI: 10.17116/jnevro20161163149-54
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural changes of lymphocytes in patients with schizophrenia treated with olanzapine

Abstract: The increased lysosome content in different lymphocyte subpopulations might contribute to the mechanism of olanzapine efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…4,5 Studies have evaluated the serotonin metabolism effects of olanzapine on platelet structure, which leads to decreases in platelet count. [6][7][8] Several case reports detail the relationship of such platelet count changes over a short period, ranging from a few days to several months. [9][10][11][12] Additionally, when platelet levels are below 10 to 20 × 10 3 /μL, the risk for spontaneous bleeding, particularly intracranial hemorrhage, increases.…”
mentioning
confidence: 99%
“…4,5 Studies have evaluated the serotonin metabolism effects of olanzapine on platelet structure, which leads to decreases in platelet count. [6][7][8] Several case reports detail the relationship of such platelet count changes over a short period, ranging from a few days to several months. [9][10][11][12] Additionally, when platelet levels are below 10 to 20 × 10 3 /μL, the risk for spontaneous bleeding, particularly intracranial hemorrhage, increases.…”
mentioning
confidence: 99%
“…Importantly, these changes were specific to SCZ but not patients with major depressive disorder (MDD), thus providing further evidence of the utility of monocyte-related markers as a distinguishing feature between these two neuropsychiatric conditions. Increased expression of a canonical activation marker, HLA-DR, was also observed in SCZ monocytes, along with changes in their phagocytic activity during acute psychotic onset [ 81 , 82 ]. Alterations in cytokine production were also observed in inflammatory mediators, such as the production of IL-1, IL-6, and tumor necrosis factor (TNF-α) [ 83 ] from SCZ monocytes, which was accompanied by a higher response to lipopolysaccharide (LPS)/toll-like receptor 4 (TLR4) stimulation [ 84 ].…”
Section: Alterations In Circulating Immune Cells In Sczmentioning
confidence: 99%
“…Consistent with this finding, some authors observed that SCZ neutrophils exhibited an increased expression of various markers of oxidative stress, such as malonaldehyde [ 122 ] and superoxide anion [ 123 , 124 ]. While several studies reported increased phagocytic activity of SCZ neutrophils, the magnitude of the observed increase differed significantly [ 81 , 124 ]. In summary, while certain details regarding the mechanistic involvement of neutrophils in various clinical aspects of SCZ pathogenesis remain to be confirmed in large-scale studies, most of the evidence suggests that these sentinel innate immune cells play an important role in peripheral immune dysfunction/inflammation in SCZ.…”
Section: Alterations In Circulating Immune Cells In Sczmentioning
confidence: 99%
See 1 more Smart Citation